The role of rational nutrition in children of all ages with anemia - Egamova Zilolaxon Burxonovna (Zien Journals, 2022)
Changes in children with anemia, various diseases that occur in them, and the importance of their dietary rheumatoid arthritis are highlighted. The resulting embryo was allowed to develop in nutrients and then inserted into her womb, where itimplanted
Keywords: anemia; WHO; hemoglobin; iron deficiency